Autophagy in Normal and Abnormal Early Human Pregnancies. (July 2015) - Avagliano, Laura; Terraneo, Laura; Virgili, Eleonora; Martinelli, Carla; Doi, Patrizia; Samaja, Michele; Bulfamante, Gaetano Pietro; Marconi, Anna Maria
Autophagy is an inducible catabolic process by which cells degrade and recycle materials to survive stress, starvation, and hypoxia. The aim of this study was to evaluate autophagy at the fetal–maternal interface, to assess autophagy involvement during the early phase of human gestation, and to explore autophagic modification in case of early abnormal pregnancy outcome. Specimens were collected from first-trimester normal gestations undergoing legal termination of pregnancy and first-trimester sporadic spontaneous miscarriages. Autophagy was studied in villous and decidual samples by transmission electron microscopy, immunohistochemistry, immunofluorescence, and Western blotting. Autophagy markers were found in cytotrophoblast, syncytiotrophoblast, extravillous trophoblast, and decidual stromal cells. Autophagy is physiologically involved in early normal gestation. Compared with normal pregnancy, spontaneous miscarriage presents an increase in autophagy expression in villous specimens due to an increment in concentration of autophagic vacuole in syncytiotrophoblast, suggesting a cytoprotective mechanism of the cells to respond to microenvironmental challenge.